Manajemen Dakwah Dalam Menghadapi Krisis Identitas Dan Spiritual Generasi Milenial: Pendekatan Psikososial Di Era Digital - Munahar, Munahar (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The rapid advancement of digital technology and the pervasive influence of social media have brought about complex challenges for the Millennial generation in forming stable identity and spiritual foundations. This study addresses the crisis of identity and spirituality among Millennials, positioning the research within the framework of psychosocial theory integrated with digital-based da’wah management. The objective is to develop an adaptive and holistic da’wah management model that effectively mitigates identity confusion and spiritual vulnerability in this era. Employing a qualitative descriptive approach, the study synthesizes literature reviews and empirical data gathered through interviews with da’wah practitioners and Millennial participants. The findings reveal that the psychosocial approach combined with strategic utilization of digital platforms fosters enhanced engagement, community building, and spiritual resilience among Millennials. This model emphasizes personalized, interactive, and contextually relevant da’wah that transforms traditional top-down messaging into participatory communication dialogues. Moreover, the study identifies the necessity for multidimensional collaboration among religious leaders, psychologists, and digital media experts to maintain program relevance and continuity. The sustained evaluation based on psychosocial and digital metrics ensures program effectiveness and improvement. In conclusion, the integration of psychosocial insights with digital da’wah management is critical in addressing the spiritual and identity crises faced by Millennials, offering a practical framework for contemporary Islamic propagation. This research contributes significantly to evolving da’wah strategies that are consonant with today’s digital and social realities, empowering Millennials as active agents of positive religious and social transformation.